Neocortex in early mammals and its subsequent variations - Kaas, Jon H. (2011)
Neocortex is an important part of the mammalian brain that is quite different from its homologue of the dorsal cortex in the reptilian brain. Whereas dorsal cortex is small, thin, and composed of a single layer of neurons, neocortex is thick and has six layers, while being variable across species in size, number of functional areas, and architectonic differentiation. Early mammals had little neocortex, with perhaps 20 areas of poor structural differentiation. Many extant mammals continue to have small brains with little neocortex, but they often have sensory specializations reflected in the organization of sensory areas in neocortex. In primates, neocortex is variously enlarged and characterized by structural and other specializations, including those of cortical networks devoted to vision and visuomotor processing.In humans, neocortex occupies 80% of the volume of the brain, where as many as 200 areas may exist.